Optimizing Plate Heat Exchanger Design for Steam Condensate Recovery Systems - Malik, Lupi Abdul; Sari, Dessy Agustina (Universitas Tribhuwana Tunggadewi Malang, 2024)
Condensate water is typically generated as a by-product during the use of steam as a medium for heat transfer. In order to optimize the transfer area, the chemical industry often employs heat exchangers, such as the plate heat exchanger (PHE), which provides flexibility in adjusting the space area for heat transfer. This case study examines the optimization of plate geometry dimensions to enhance the heat transfer process of PHE equipment design. The optimization process involves mathematical equations and a literature review of the design of this type of heat exchanger. Improving the dimensional aspect of the plate geometry results in an increase in the overall heat transfer coefficient (U) and a reduction in the number of design requirements used. The study's estimation results suggest that the PHE design has a limitation on plate dimensions, which should be less than 0.3Ã—0.6 m. Additionally, it is important to consider the pressure drop value, which should not exceed 29.07 kPa. A review of the chemical industry field provided estimated options for plate size and quantity, both of which support the optimization of heat transfer rate and design constraint thresholds. The implementation of the design has been found to enhance the performance of the planning process for recovering steam condensate water.